1991
DOI: 10.1128/jb.173.22.7395-7400.1991
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hisT-mediated tRNA pseudouridylation results in a uracil requirement that interferes with Escherichia coli K-12 cell division

Abstract: We show that hisT function is required for normal growth of Escherichia coli K-12, since a lack of hisT-mediated pseudouridine tRNA modification causes a uracil requirement that interferes with cell division. We also show that hisT transcription is positively growth rate regulated in exponentially growing bacteria and is induced during the transition from exponential to stationary growth phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…Considering that W is so abundant and so widely distributed in naturally occurring RNAs, and that so much genetic information (in the form of W synthases and snoRNAs) is invested in its formation, it is a reasonable conjecture that this modi ed nucleoside is an important, even essential, constituent of RNA in the biological contexts in which it normally exists. The profound phenotypic effects seen in some cases of W de ciency in RNA (40,54,64) fully support this view. Particularly telling in this regard are those genetic experiments in which loss of one or more W residues has little or no discernible effect on growth and other measurable parameters, yet the mutant strain is unable to compete effectively with the parent strain in mixed-culture experiments.…”
Section: Discussionsupporting
confidence: 67%
“…Considering that W is so abundant and so widely distributed in naturally occurring RNAs, and that so much genetic information (in the form of W synthases and snoRNAs) is invested in its formation, it is a reasonable conjecture that this modi ed nucleoside is an important, even essential, constituent of RNA in the biological contexts in which it normally exists. The profound phenotypic effects seen in some cases of W de ciency in RNA (40,54,64) fully support this view. Particularly telling in this regard are those genetic experiments in which loss of one or more W residues has little or no discernible effect on growth and other measurable parameters, yet the mutant strain is unable to compete effectively with the parent strain in mixed-culture experiments.…”
Section: Discussionsupporting
confidence: 67%
“…In this context, we have begun comprehensive experimentation on the proposal outlined in this paper. The finding that U-to-v conversion in tRNA has pleiotropic effects of much greater magnitude than previously suspected [61] is fully consistent with our view about the potential importance of U-to-ly conversion in rRNA.…”
supporting
confidence: 91%
“…Pseudouridine sequencing analysis of three of the suppressed strain isolates+ RNA from isolates 1, 3, and 6 were analyzed along with RNA from MG1655 as a positive control+ Conditions were as in Figure 4+ mutation reduces the activity of RNase PH, the gene product, to very low levels, and also reduces the level of orotate phosphoribosyltransferase, encoded by pyrE, because of close coupling between the two genes (Jensen, 1993)+ This fact is relevant to our studies because Tsui et al+ (1991) showed that disruption of the truA gene, which makes a ⌿ synthase for tRNA, causes a 3-4-fold reduction in growth rate when present in strain MG1655 and related strains+ Inhibition of growth was observed in minimal medium but virtually disappeared when uracil was added (Tsui et al+, 1991)+ Moreover, there was no inhibition of growth in rich medium (Tsui et al+, 1991; M+ Winkler, pers+ comm+)+ Jensen (1993) suggested that the growth defect is due to the rph mutation in MG1655 that in turn affects pyrimidine synthesis by down-regulation of the pyrE gene+ Despite the fact that this effect was only seen in minimal medium and was absent in rich (LB) medium, whereas our experiments were done entirely in the same rich medium where no effect should be anticipated, we have directly examined the effect of the rph gene by the following gene transfer experiment+ P1 transduction from MH040 was repeated using as recipient strain CA244, which is known to be rph ϩ (Reuven & Deutscher, 1993), and strain VH1000, which is MG1655 in which the rph mutation has been repaired+ MG1655 was included as a recipient to serve as a tiny colony control+ In all three cases, chloramphenicolresistant, poorly growing colonies were found+ When replated and grown for 18 h at 37 8C, only tiny colonies were obtained, like Mutant/pTRC in Figure 6+ As a growth control, the rescued strain MG1655(rluD Ϫ )/ pTrc99A(rluD ϩ ), which grows normally in the presence of chloramphenicol, was used, and in the same time interval yielded the same normal colony pattern shown in Figure 6+ …”
Section: Growth Of the Rlud-disrupted Strainmentioning
confidence: 99%